The Papers of Thomas Jefferson: Retirement Series, Volume 15 : 1 September 1819 to 31 May 1820 - Jefferson, Thomas, 1743-1826 (Book collections on Project MUSE., 2019)
The 618 documents in this volume span 1 September 1819 to 31 May 1820. Jefferson suffers from a "colic," recovery from which requires extensive rest and medication. He spends much time dealing with the immediate effects of the $20,000 addition to his debts resulting from his endorsement of notes for the bankrupt Wilson Cary Nicholas. Jefferson begins to correspond with his carpenter, the enslaved John Hemmings, as Hemmings undertakes maintenance and construction work at Poplar Forest. Jefferson and his allies in the state legislature obtain authorization for a $60,000 loan for the fledgling University of Virginia, the need for which becomes painfully clear when university workmen complain that they have not been paid during seven months of construction work. In the spring of 1820, following congressional discussion leading to the Missouri Compromise, Jefferson writes that the debate, "like a fire bell in the night, awakened and filled me with terror," and that with regard to slavery, Americans have "the wolf by the ear, and we can neither hold him, nor safely let him go."